1985
DOI: 10.1063/1.334517
|View full text |Cite
|
Sign up to set email alerts
|

Shallow boron-doped junctions in silicon

Abstract: Shallow boron-doped junctions in silicon have been investigated by means of secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy, spreading resistance profiling, and four-point probe techniques. The junctions were formed by implanting BFt ions into n-type Si at the dose range of 1-5 X 10 15 ions/cm 2 , through a thin (25-nm) screen layer of silicon dioxide. We have emphasized the higher dose range (3-5 X 10 15 ions/cm 2 ) as it is more relevant to processes in the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Figure 4 indicates that such a time difference is insufficient to significantly impact the activation of boron atoms at this temperature. [37][38][39][40] Hence the presence of higher surface boron concentrations cannot be the reason for the higher surface acceptor concentration observed for thicker films. Given the similar concentrations of boron and Al in the thinner and thicker films, it is clear that the source of increased acceptor doping lies elsewhere.…”
Section: Conductance Spectroscopy Measurements Of Aln/si Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 indicates that such a time difference is insufficient to significantly impact the activation of boron atoms at this temperature. [37][38][39][40] Hence the presence of higher surface boron concentrations cannot be the reason for the higher surface acceptor concentration observed for thicker films. Given the similar concentrations of boron and Al in the thinner and thicker films, it is clear that the source of increased acceptor doping lies elsewhere.…”
Section: Conductance Spectroscopy Measurements Of Aln/si Interfacesmentioning
confidence: 99%
“…While thicker films are exposed to the higher growth temperature for longer times (300 seconds of additional exposure duration at 1050°C for the 200 nm AlN sample compared to the 50 nm sample), prior reports on the activation of ion-implanted boron in crystalline Si indicates that such a time difference is insufficient to significantly impact the activation of boron atoms at this temperature. [37][38][39][40] Hence the presence of higher surface boron concentrations cannot be the reason for the higher surface acceptor concentration observed for thicker films.…”
Section: The Physical Origin Of Increased Surface Acceptor Concentrationmentioning
confidence: 99%
“…In this paper we analyze the data of these studies [especially the SIMS work (1), because of its higher spatial resolution] in terms of a model based on the wellknown isotopic exchange process between '802 gas molecules and the 160 network atoms of silica glass (5). This analysis is similar in principle to that applied earlier by Revesz and Hughes (6) to the data of Rochet et al (3). We show that results of calculations based on this model reasonably well reproduce the spatial and temporal evolution of the '80 concentration profiles observed by the SIMS measurements.…”
Section: On the Mechanism Of Interaction Between 1802 Gas Andmentioning
confidence: 93%
“…There have been several recent studies which have used SIMS or nuclear reaction microanalysis techniques to examine the interaction between '80~ molecules and films of Si'sO2 thermally grown on silicon (1)(2)(3)(4). These studies have shown that an oxide film consisting predominantly of '80 atoms forms at the Si/SiO2 interface and that ~sO atoms are incorporated into the outer surface region of the Si'602 film.…”
Section: On the Mechanism Of Interaction Between 1802 Gas Andmentioning
confidence: 99%
See 1 more Smart Citation